Land Use Change Mapping in Coastal Areas Subdistrict South Bontang, Bontang, East Kalimantan Province And Its Impact on Socio-Economic Aspects - Ilman Yusra, Arief; Windupranata, Wiwin; Wisayantono, Dwi (Indonesian Journal of Geospatial, 2013)
Abstract. The coastal area is a center of social activity and economic activity. As a center of social and economic activities, the coastal areas are potential areas to be developed and utilized as a result that there will be changes and land uses in the form of land use. Land use is a form of physical influence of human activities on the earths surface. Land use of an area associated with population growth and activity. The increasing population and the more intense activity in the population of a region on the increasing impact of land use change. To view and control the land use changes land use monitoring needs to be done at a certain time. Monitoring of land use can be done by identifying and interpreting information from remote sensing data in the areas of land use that will be monitored. By comparing the two forms of land use from remote sensing data of different time at the same location, will be obtained by changes in land use as well as statistical data coupled with social and economic conditions. It can be in terms of changes in the land analysis to the socio-economic aspects of the local population. The results showed that land use changes with the addition of the largest area occurs on the settlement in the amount of 43.05 Ha while, land use changesÂ  with the greatest reduction occurred in the vast open land in the amount of 93.08 Ha. Land use changes had positive impact on social aspect with increasing population of that work as many as 21,538 people and economic aspects with poverty who reduced amounted to 1.55%.Â Keywords : Land Use, Land Use Change, Social Economy, Coastal Area